(untitled) (Intent Research Scientific Journal, 2023)
The article reveals the concept of problem-based learning in universities in modern conditions set by the requirements of the Federal State Educational Standards and modern society. Methods: research, analytical. Results: recommendations on ways to transform and form the creative ability of the individual.